Child-Protection Systems – Croatian Perspective - Šimović, Ivan; Čulo Margaletić, Anica; Preložnjak, Barbara (Child-Protection Systems, 2025)
Abstract:The child protection system in the Republic of Croatia reflects the spirit and letter of the fundamental principles prescribed in global and regional legal sources that represent a component of the national legal order. These sources include the CRC, ECHR, ECECR, Charter, etc. Such high standards of child protection require adjustment of the legal, educational, public finance, healthcare and social welfare systems to form an inherent, functional and effective framework of the child protection system. The goal of this report is to present a comprehensive analysis of all relevant instruments the Croatian legislator has used in the context of realisation of the national child protection system. Keywords: child protection, child at risk, authority measures, child’s participation rights, parental responsibility